Type IV secretion system is not involved in infection process in citrus - Jacob, Tiago Rinaldi [UNESP]; Laia, Marcelo Luiz de; Moreira, Leandro Marcio; Gonçalves, Janaína Fernandes; Carvalho, Flavia Maria de Souza; Ferro, Maria Inês Tiraboschi [UNESP]; Ferro, Jesus Aparecido [UNESP] (International Journal Of Microbiology, 2014)
The type IV secretion system (T4SS) is used by Gram-negative bacteria to translocate protein and DNA substrates across the cell envelope and into target cells. Xanthomonas citri subsp. citri contains two copies of the T4SS, one in the chromosome and the other is plasmid-encoded. To understand the conditions that induce expression of the T4SS in Xcc, we analyzed, in vitro and in planta, the expression of 18 ORFs from the T4SS and 7 hypothetical flanking genes by RT-qPCR. As a positive control, we also evaluated the expression of 29 ORFs from the type III secretion system (T3SS), since these genes are known to be expressed during plant infection condition, but not necessarily in standard culture medium. From the 29 T3SS genes analyzed by qPCR, only hrpA was downregulated at 72 h after inoculation. All genes associated with the T4SS were downregulated on Citrus leaves 72 h after inoculation. Our results showed that unlike the T3SS, the T4SS is not induced during the infection process.